UPR-Activated IRE1 Signaling Pathway Promotes Malignant Growth of Breast Cancer - Fan, Xinyu; Zhu, Zhiqi; Zhao, Ziyi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Initially, it was believed that the unfolded protein response (UPR) was a network signal that synchronized apoptotic and adaptive responses to the buildup of unfolded proteins in the endoplasmic reticulum (ER). The endoplasmic reticulum stress sensor IRE1 is a major player in the UPR, and overactivation of IRE1 can promote a variety of pathological phenomena, such as diabetes, neurodegenerative diseases, and cancer. Under endoplasmic reticulum stress, IRE1 is activated through autophosphorylation and oligomerization, leading to conformational changes in the RNase domain, thereby promoting two signaling pathways: 1) unconventional splicing of XBP1 and 2) regulated IRE1 dependence Decay (RIDD). Research has revealed that aggressive B-type breast cancer cells typically have an overexpressed and amplified IRE1 gene. Through the RIDD mechanism, IRE1 processes and regulates the breakdown of a fraction of tumor-suppressing micro-RNA, which in breast cancer cells results in the Ras oncogene GTPase. RAB3B is elevated. This article reveals the mechanism of action of the IRE1 signaling pathway and the RIE1-RIDD-miRNA pathway in promoting the malignant development of luminal breast cancer.